Intrathecal hydromorphone for analgesia after partial hepatectomy: a randomized controlled trial. Issue 11 (17th August 2022) - Ding, Lin; Chen, Dongxu; Chen, Yu; Wei, Xiongli; Zhang, Yabing; Liu, Fei; Li, Qian
Abstract : Introduction: There is substantial interest in adding intrathecal opioids, such as hydromorphone to the multimodal pain management strategies. We conducted a randomized controlled trial to examine whether adding intrathecal hydromorphone to a multimodal strategy could safely improve analgesic efficacy for patients undergoing partial hepatectomy. Methods: A total of 126 adult patients undergoing partial hepatectomy under general anesthesia were randomly assigned to receive intrathecal hydromorphone (100 μg) or no block. The primary outcome was the incidence of moderate to severe pain during movement at 24 hours after surgery. Secondary outcomes included the incidence of moderate to severe pain during rest or movement at different times within 72 hours, pain scores during rest or movement within 72 hours after surgery, analgesic use, adverse events, and indicators of postoperative recovery. Results: Among the 124 patients analyzed, the intrathecal hydromorphone group showed a lower incidence of moderate to severe pain during movement at 24 hours after surgery (29.0% vs 50%; RR 0.58, 95% CI 0.37 to 0.92) than the control group. However, the absolute difference in pain scores on a numerical rating scale was less than 1 between the two groups at 24 hours after surgery. Mild pruritus within the first 24 hours after surgery was more frequent in the intrathecal hydromorphone group (19.4% vs 4.8%; p=0.01). Discussion: Intrathecal hydromorphone 100 μg reduced the incidence of moderate to severe pain and pain scores during movement within 24 hours after partial hepatectomy. However, the difference in pain scores may not be clinically significant, and intrathecal hydromorphone 100 μg did not significantly improve other analgesic or functional outcomes. Further investigation is needed to optimize the intrathecal hydromorphone dose. Trial registration number: ChiCTR2000030652.